A service plan for Philippine Airlines' Domestic Airport Procedure - Cruz, Maria Jesusa P. (Animo Repository, 2004)
Philippine Airlines is still the leading service provider of domestic passenger air transportation. However, the proponents learned that the main challenge being faced by the company is meeting the demands of the Rehabilitation Plan. In particular, the cost of debt servicing requires the company to earn more in order to defray such payments. In that light, the proponents, after two months of in-depth study, have come-up with a proposition that would help the company gain more revenue. This is for the purpose of creating a potential source of fund which will be used to pay its debts. After paying such debts, the company is expected to operate with more ease, thus it can spend on service improvements. This service improvement will eventually lead to achieving the proposed ultimate goal which is TO BE THE MOST PREFERRED DOMESTIC AIR PASSENGER CARRIER. However, due to time limitations, the proponents have chosen to work only on a service development program on airport procedures. Since this is procedural, minimal costs are attached. These programs are expected to have an immediate effect in our short-term objective, which is to increase passenger traffic by 6%. And lastly, a year-end overall evaluation would be prepared to match target cost benefits to actual cost benefits.